Modernism as Projected through the Character of Vladimir in Samuel Beckett's Waiting for Godot - Shanon, Eileen; Wijanarka, Hirmawan (Journal of Language and Literature, 2016)
Samuel Beckett’s Waiting for Godot, a play published in 1948, not long after the break of World War II, displays absurdity through its theme, plot, setting and characters. Despite the postmodern label on the literary work itself, this article assumes that there are ideas of modernism contained within it, projected through the character of Vladimir. Six characters are analyzed in this study. They are Vladimir, Estragon, Pozzo, Lucky, and the Boy. Among these characters, Vladimir tends to be more of a modernist rather than a postmodernist. This is shown in his act of waiting for Godot while the others do not really concern about the relevance of Godot in determining the outcome of their fates. Vladimir rests his faith and hope in Godot, persuading his fellow tramp Estragon to accompany him during his wait. Vladimir’s critical thinking and quest for answers give a clear place to stand for the other characters who don’t present the importance of logical thinking. Vladimir stands out as a character with modernist values such as anticipating, reasoning, and relevant discoursing. Keywords: modernism, postmodernism, Samuel Beckett